Monotherapy with biologic disease-modifying anti-rheumatic drugs in rheumatoid arthritis. (20th August 2016) - Choy, Ernest; Aletaha, Daniel; Behrens, Frank; Finckh, Axel; Gomez-Reino, Juan; Gottenberg, Jacques-Eric; Schuch, Florian; Rubbert-Roth, Andrea
Abstract: Current EULAR guidelines state that biologic DMARD (bDMARD) therapy should be administered in combination with MTX or other conventional synthetic (cs) DMARD in RA. Nonetheless, a third of patients for whom a bDMARD agent is prescribed take it in the absence of concurrent csDMARD therapy. While the reasons underlying the low uptake of bDMARD–csDMARD combination therapy in clinical practice have not been well delineated, they may include poor adherence, contraindication to csDMARD therapy and adverse effects, as well as csDMARD withdrawal following remission. The challenges surrounding bDMARD therapy and the benefit/risk ratio of biologic monotherapy when compared with combination with a csDMARD will be discussed. We will provide insights into these important issues, as well as reviewing the evidence base differentiating biologic agents and exploring therapeutic options for patients with rheumatoid arthritis for whom csDMARD therapy is contraindicated or discontinued.